Tenofovir Alafenamide (TAF) as Long-Term Therapy for Chronic Hepatitis B: Is It the Best Choice? - Hasan, Irsan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
-